Knowledge Management and Digital Transformation through Industrial Engineering and Civil Engineering Perspectives - Meilani, H C Ho, K E N Soebandrija, S Wong (International Journal of Advanced Science and Technology, 2020)
Knowledge management constitutes one of trends in digital economy era. The mentioned digital economy era is characterized by sophistication of human interaction, computing and content to provide interactive information highway. The objective of this paper is to ensure strategic implementation of knowledge management (KM) and digital transformation (DT) through theoretical perspectives of Industrial Engineering (IE) and Civil Engineering (CE). The strategic implementation in this paper is applicable within empirical perspective in PT. Wijaya Karya (Persero) Tbk, known as one of State Own Enterprises (SOE) in Indonesia, namely WIKA. Result of this paper refers to the bibliometric analysis of KM; and its vital role in DT through IE and CE perspectives. Subsequently, the mentioned result is implemented strategically in WIKA through its value of Agility (Change, Focus, Fast), Caring (Accountable, Respect, Safety Oriented) and Excellence (Commitment, Innovation, Professional). Discussion of this paper refers to strategic perspective to ensure implementation of KM and DT through theoretical perspectives of IE and CE. Meanwhile, the research methodology in this paper elaborates the quantitative approach through research model. This model involves variables of Perceived Usefulness (PU), and Perceived Ease of Use (PEOU) that influences Attitude Toward Using (ATU) that ultimately influences Actual System Usage (ASU).